Determinants of foreign exchange reserves holdings in East-Asia, Pacific and South Asia - BOU, Sovanpich (KDI School, 2018)
The main purpose of this study is to find the significant determinants of foreign exchange reserves holdings in East-Asia, Pacific, and South Asia using Panel Fixed Effect model of 10 countries in lower middle income group in these regions. Our study has found that the size of the economy, trade openness, financial openness and external debts increase reserves holdings while the economic wellbeing of the people and the appreciation of real effective exchange rate decrease the central banks’ incentives to accumulate international reserves.
Thesis(Master) --KDI School:Master of Public Policy,2018